ANALISIS MUATAN PENDIDIKAN KARAKTER DALAM BUKU TEKS KURIKULUM 2013 KELAS III SD SEMESTER 1 - Yogi Kuncoro Adi (Universitas Muhammadiyah Surakarta, 2017)
The aim of this study is to describe character education content of the third grade elementary school curriculum 2013 textbook semester 1. The design of this study was content analysis by qualitative approach. Subject of this study is textbook of curriculum 2013 semester 1 for the third grade of elementary school students. Object of this study is character education content. The data collected by reading and recording of unit analysis. The unit analysis were materials and evaluation that integrated the values of character education in the textbooks. The instrument used in this research was the analysis sheet based on the theories. The validity of the instrument and the data used was semantic validity and expert judgment. The reliability of the data used the stability and reproducibility. The techniques of analyzing data consisted of unitizing, sampling, recording, reducing, inferring, and narrating. The results of this study show that most of the character education value was spread into every theme, although some indicators were not found. Distribution of each character value, by disregarding any indicators, evenly on all themes. However, these findings prove that a particular character value investment is not focused as in the relevant theory. Keywords: analysis, character education content